2010
DOI: 10.1093/ndt/gfq500
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor expression in monocytes in patients with chronic kidney disease and haemodialysis: relation with inflammation

Abstract: The percentage of CD14( +) monocytes expressing TLR-2 were similar in all of the study groups, whereas the percentage of CD14( +) monocytes expressing TLR-4 were significantly lower in both stage 3-4 CKD and HD patients at baseline than in controls. The mean fluorescence intensities (MFI) of TLR-2 were significantly lower in controls than in stage 3-4 CKD and HD patients at baseline. The MFI of TLR-4 was similar in all of the groups. The percentage of CD14( +) monocytes expressing TLR-2 did not change during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 31 publications
1
38
0
2
Order By: Relevance
“…Our results are in accordance with the results of Koc et al [11], but in contrast to those of Ando et al [2] who showed a significant reduction of TLR4 expression in predialysis CKD patients compared with healthy controls. The reason for this discrepancy is not clear.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in accordance with the results of Koc et al [11], but in contrast to those of Ando et al [2] who showed a significant reduction of TLR4 expression in predialysis CKD patients compared with healthy controls. The reason for this discrepancy is not clear.…”
Section: Discussionsupporting
confidence: 93%
“…Existing evidence shows that TLR2 and TLR4 are involved in the pathogenesis of CKD-related complications in hemodialysis patients [11,12,13] and predialysis CKD patients, though not in all studies [2,11]. Furthermore, patients with diabetes mellitus types 1 and 2 have shown increased monocyte expression of TLR2 and TLR4 [14,15], and a recent study has demonstrated in vitro upregulation of TLR4 expression in the renal tubules of human kidneys with DN [16].…”
Section: Introductionmentioning
confidence: 99%
“…TLR4 signaling pathways and their expression have been studied in relation to inflammation in kidney injury [6], [50]. We examined the gene and protein expression of TLR4 in the kidney cortical tissues of animals from all experimental groups.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with end-stage renal disease (ESRD) exhibit upregulated basal expression of Toll-like receptors (TLRs) including TLR-2 and TLR-4, up-regulated expression of integrin, and increased basal production of cytokines and reactive oxygen species (ROS) on polymorphonuclear neutrophils (PMNs) and monocytes. [4][5][6] Besides the property of spontaneous activation, PMNs and monocytes are also accompanied with impaired phagocytic capacity which *These two authors contribute to this paper equally.…”
Section: Introductionmentioning
confidence: 99%